Strategi Dakwah Majelis Wakil Cabang Nahdatul Ulama (MWCNU) Dalam Mengubah Perilaku Masyarakat di Kecamatan Sungai Lilin Musi Banyuasin - Farham Ali Maslehar; Candra Darmawan (Social Science and Contemporary Issues Journal, 2023)
This research is entitled: "Da'wah Strategy of the Representative Branch Council of Nahdlatul Ulama (MWCNU) in Changing Community Behavior in Sungai Lilin Musi Banyuasin District". The issues discussed in this thesis are: What are the effective da'wah strategies carried out by the Nahdatul Ulama Branch Representative Council (MWCNU) in changing community behavior in Sungai Lilin Musi Banyuasin District as well as external and internal obstacles in changing community behavior. The aim of this research is: To determine the effective da'wah strategy carried out by the Nahdatul Ulama Branch Representative Council (MWCNU) as well as the external and internal obstacles in changing community behavior in Sungai Lilin Musi Banyuasin sub-district. This research uses qualitative research. The data collection technique in this research uses interview, observation and documentation methods. The theory used in this research is the theory of Drs. Samsul Munir Amin. The data analysis technique used in this research is the technique from Miles and Huberman, namely data reduction, data presentation and drawing conclusions. The results of the research show that the da'wah strategy activities carried out by the Nahdatul Ulama Branch Representative Council (MWCNU) in changing people's behavior have been implemented well. The implementation of this da'wah strategy activity is carried out well by using Bi-Lisan Da'wah, Bi-Hal Da'wah and Bi-Qalam Da'wah as well as supporting and inhibiting factors in carrying out the da'wah. Planning good da'wah activities can of course pay attention to the object of da'wah who always listens and pays attention to what a da'i says. So that it can create self-awareness in a mad'u to carry out the teachings of the Islamic religion without any element of coercion.